Neural network for rainfall runoff modelling - Hafiz Fadillah, Alhadi (University Malaysia Sarawak, UNIMAS., 2004)
Neural network is a very useful data modelling tool that is able to capture and represent complex input and output relationships. The advantage of neural network lies in its ability to represent both linear and non-linear relationships and also its ability to learn these relationships directly from the data being modelled. So, the purpose of this study is to develop a rainfall runoff model for Sungai Tinjar with outlet at Long Jegan, The network was trained using Back Propagation Algorithm.